THE EFFECTIVENESS OF MAPPING WORD IN TEACHING VOCABULARY AT THE TENTH GRADE OF STUDENTS OF SMK HASSANNUDIN PARE - Ary Setya Budhi Ningrum; Eti Kurniasari (Pusat Pengembangan Bahasa IAIN Tulungagung, 2014)
The purpose of the study was to determine the effectiveness of mapping word as a strategy in teaching vocabulary for the tenth grade students of SMK Hassanuddin Pare. By conducting a quasi-experimental investigation, two out of three existing classes at computer technique class of SMK Hassanuddin Pare in the academic year 2013/2014 were selected by a lottery to experimental and control group. For analyzing the data, Analysis of covariance (ANCOVA) were utilized by using students’ pre-test score as the covariate variable. The result finding revealed that there is a significant difference on the students’ means score between the experimental and the control groups as evidenced by F(1, 37) = 13.930, p (.001 ) < a (.05). Since the experimental group has the higher means score than the control group; it can be inferred that students who are taught using mapping word have better vocabulary mastery than those taught using non-mapping word. Thus, it can be concluded that using mapping word to teach vocabulary at SMK HASSANUDIN Pare is better than using conventional method.